Protective efficacy of statins in patients with Klebsiella pneumoniae bloodstream infection - Xu, Qian; Zheng, Beiwen; Shen, Ping; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2023)
Background Patients with bloodstream infection of Klebsiella pneumoniae (BSI-KP) have a high risk of death and septic shock. This study aims to identify the risk factors for mortality and severity in patients of BSI-KP. Methods Data of BSI-KP patients were extracted from the MIMIC IV (Medical Information Mart for Intensive Care IV) database, and patients infected with only K. pneumoniae in blood were included in this study. The risk factors of 28-day mortality and septic shock in BSI-KP patients were analyzed, respectively. Results A total of 279 patients enrolled and the all-cause 28-day mortality rate was 11.8%. The use of statins (OR 0.220, 95% CI 0.060-0.801, p = 0.022) and quinolones (OR 0.356, 95% CI 0.143-0.887, p = 0.027) were both independent protective factors for death within 28 days, while the use of vasoactive drugs (OR 7.377, 95% CI 1.775-30.651, p = 0.006) was a risk factor. Besides, pulmonary disease (OR 2.348, 95% CI 1.126-4.897, p = 0.023), bleeding and coagulation disorders (OR 3.626, 95% CI 1.783-7.372, p < 0.001), respiratory failure (OR 2.823, 95% CI 0.178-6.767, p = 0.020) and kidney dysfunction (OR 2.450, 95% CI 1.189-5.047, p = 0.015) were independent risk factors for patients suffered from septic shock while hypertension was a protective one. The receiver operating characteristic (ROC) curves could well predict the risk of death within 28-day (area under ROC = 0.855, 95% CI = 0.796–0.914, p < 0.001) and septic shock (AUROC = 0.815, 95% CI = 0.755–0.874, p < 0.001) in patients with BSI-KP. Conclusion The use of statins could decrease the risk of 28-day mortality in patients of BSI-KP. The risk factor-based prediction model provided evidence for drug treatment in BSI-KP patients. Paying more attention to the strategy of drug treatment will be an optimal way to improve patient’s outcome in clinical practice.